Effect of Administration of the Ovaspec Hormone with Different Doses on the Reproduction of Dumbo Catfish (Clarias gariepinus) - Ahmad Diansyah; Muhammad Junaidi; Bagus Dwi Hari Setyono (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
African catfish are freshwater fish that have long been cultivated in Indonesia. African catfish grow quickly, are highly resilient to environmental conditions, and reproduce rapidly. The critical phase in producing fish fry is the larval stage, during which the fry reach the post-larval stage (fry) and measure 1-3 cm. Fish spawning can be accelerated by manipulating conditions, such as injecting hormones into the fish. Therefore, when conducting artificial spawning, it is important to know the correct hormone type and dosage. The aim of this research was to determine the effects of different ovaspec injection doses on spawning time, egg hatchability, and survival of African catfish (Clarias gariepinus) larvae. This research used a Completely Randomized Design (CRD) with 4 treatments repeated 3 times. The treatments in this study used different doses of Ovaspec. The ovaspec dose is 0 ml/kg, the ovaspec dose is 0.4 ml/kg, the ovaspec dose is 0.6 ml/kg, and the ovaspec dose is 0.8 ml/kg. The parameters calculated are spawning latency, fecundity, egg hatchability, larval survival and water quality. The results of this study show that the ovaspec hormone can influence the latency to spawning, egg hatchability and survival of African catfish larvae. The best dose in this study was 0.4 ml/kg, which resulted in an average fastest spawning latency of 521.33 minutes, egg hatchability of 84.47%, and larval survival of 77%.